Why it's so hard? Exploring social barriers for the deployment of thermal energy storage in Spanish buildings. (June 2021) - Simó-Solsona, M.; Palumbo, M.; Bosch, M.; Fernandez, A.I.
Abstract: Thermal energy storage (TES) has been a prominent topic of scientific and industrial research for the last decades as TES increases efficiency, reliability and economic feasibility of solar energy systems. Several TES technologies are today feasible and competitive from a scientific-technical, sustainable and economic point of view. However, the social awareness and acceptance of TES has not followed such a development, as socio-cultural and legal aspects to be considered for their broader implementation hinder it. The main objective of this paper is to analyse social and cultural barriers to TES adoption in the Spanish context. For this proposal, we use quantitative and qualitative data provided from professionals and experts of the building sector. Hereby the main ideas arising from the analysis: the economic crisis of 2008 and the poor condition of the existing building stock prevent the adoption of extensive retrofitting measures including energy efficiency solutions such as TES' while TES is regarded as an emerging market in Mediterranean climates such as Spanish. The lack of expertise of professionals hinders the transmission of TES benefits to occupants. Besides, there is little dissemination of good practices and professionals are suspicious of the long term performance of such technologies.